2018
DOI: 10.1530/edm-18-0006
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent primary hyperparathyroidism and pheochromocytoma in a Chinese lady with neurofibromatosis type 1

Abstract: SummaryWe report a case of elderly Chinese lady with neurofibromatosis type-1 presenting with longstanding palpitation, paroxysmal hypertension and osteoporosis. Biochemical testing showed mild hypercalcaemia with non-suppressed parathyroid hormone level suggestive of primary hyperparathyroidism, and mildly elevated urinary fractionated normetanephrine and plasma-free normetanephrine pointing to a catecholamine-secreting pheochromocytoma/paraganglioma. Further scintigraphic investigation revealed evidence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…The prevalence of Pheo in patients with NF1 is more important in patients with hypertension in general population, 1.0%-5.7% versus 0.2-0.6% and even higher rates are in those with NF1 and hypertension at 20%-50% [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Two prospective studies showed higher prevalence of Pheo in which patients with NF1 were screened for Pheo (7.7% [3] and 14.6% [22]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of Pheo in patients with NF1 is more important in patients with hypertension in general population, 1.0%-5.7% versus 0.2-0.6% and even higher rates are in those with NF1 and hypertension at 20%-50% [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Two prospective studies showed higher prevalence of Pheo in which patients with NF1 were screened for Pheo (7.7% [3] and 14.6% [22]).…”
Section: Discussionmentioning
confidence: 99%
“…NF1 patients should undergo screening for this affections especially when associated with catecholamine-symptoms or hypertension [25]. The mean age at the moment of diagnosis was reported between the age of fourty and fifty in some studies [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, patients were diagnosed with metaphyseal bone lesions (defects/NOF) who also had developed neurofibromas (104) and fulfilled the current diagnostic criteria of NF1 (40,106). The clinical diagnosis of the skeletal findings as lesions associated with NF1 requires the exclusion of endocrine disorders (52,46,47,112). Meanwhile, the simultaneous occurrence of CGCG of the jaw and NOF of the long bones in cases with NF1 has been described in detail [40, 53 (in the latter case, jaw lesion was initially diagnosed as GCT)].…”
Section: Cgcg Of Jaws In Nf1mentioning
confidence: 99%
“…An increased frequency of various endocrine pathologies, such as central precocious puberty, short stature, diencephalic syndrome, growth hormone deficiency or growth hormone hypersecretion has been reported in children. In addition, pheochromocytoma, parathyroid carcinoma, parathyroid adenoma, somatostatin producing neuroendocrine tumor, duodenal carcinoid tumor producing somatostatin, thyroid papillary carcinoma with pheochromocytoma have been described in patients with NF1 ( 1 , 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%